Strategi Pelestarian Seni dan Budaya Nusantara Melalui Pendidikan Pada Anak-Anak Indonesia di Malaysia - Andriani, Resti; Al jannah, Dina Masfufah; Sari, Inelea; Ramadhanty, Masayu Elmarisa; Ardiansyah, Fiki; Dwiyanti, Atika (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This Community Service Program (KKN) is a form of service to the community and nation, not only in Indonesia but also to the Indonesian people in Malaysia. This program aims to introduce and preserve Indonesian arts and culture to Indonesian migrant children in Malaysia. Learning is given in the form of theory and practice. Art and cultural activities implemented in Malaysia include the introduction of traditional dance, folk songs, batik drawing, and traditional games. The results showed that the children were very fond and enthusiastic in the introduction and practice of Indonesian arts and culture.